6y+5=6y-y

Simple and best practice solution for 6y+5=6y-y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6y+5=6y-y equation:


Simplifying
6y + 5 = 6y + -1y

Reorder the terms:
5 + 6y = 6y + -1y

Combine like terms: 6y + -1y = 5y
5 + 6y = 5y

Solving
5 + 6y = 5y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-5y' to each side of the equation.
5 + 6y + -5y = 5y + -5y

Combine like terms: 6y + -5y = 1y
5 + 1y = 5y + -5y

Combine like terms: 5y + -5y = 0
5 + 1y = 0

Add '-5' to each side of the equation.
5 + -5 + 1y = 0 + -5

Combine like terms: 5 + -5 = 0
0 + 1y = 0 + -5
1y = 0 + -5

Combine like terms: 0 + -5 = -5
1y = -5

Divide each side by '1'.
y = -5

Simplifying
y = -5

See similar equations:

| Y=x^3-12x | | 5(x+-9)=-135 | | 3(5x-9)=21y | | 2x+3y=147 | | y^2+2y-4= | | 5x-6(x-5)=2(x+5)+(x-4) | | 50=X+2(X+2) | | 2x^4+x^3+x^2+x-1=0 | | -16t^2+48t-64=0 | | 3(-3)+10= | | G(x)=x^3-12x | | 2(p-5)-7-4p= | | x*9-53=x*5-5 | | 2(x+-5)=-95 | | 7p-4=2(10p-10)+6(-10+p) | | log(x+2)=1+log(4x+3) | | 2u^3= | | 3(4z+6)-32= | | 2x+-5=-95 | | 9(2X-5)=5(X+5)+4 | | -9r=20+1r | | 6+66x=44x+12 | | X(2y+3)=28 | | 2(1+3x)=5(x-3) | | 240=29-x | | 7x-54+72+72=180 | | 3y+(7+y)=31 | | -4.1=8.7(y-9.7) | | 7x-54+72=180 | | -6a+3=-12 | | 45+63+x=180 | | 63+45+(x-1)=180 |

Equations solver categories